Investigating the in vitro bioaccessibility of polyphenols in fresh and sun‐dried figs (Ficus carica L.). (17th July 2013) - Kamiloglu, Senem; Capanoglu, Esra
Summary: In this study, in order to evaluate the in vitro bioaccessibility of fresh and sun‐dried figs, total antioxidant capacity (TAC), total proanthocyanidin content (TPA) and the major phenolic compounds were determined at different phases of simulated gastrointestinal (GI) tract digestion for Sarilop and Bursa siyahi fig varieties. Four major phenolic compounds (chlorogenic acid, rutin, cyanidin‐3‐glucoside (C3G) and cyanidin‐3‐rutinoside (C3R)) were investigated for GI tract digestion. The results of in vitro GI tract digestion revealed that the dialysed fraction (IN) represented 9–26% and 1–22% of the initial TAC of the whole‐fresh yellow and purple figs, respectively. Moreover, in case of 2, 2‐azinobis(3‐ethylbenzothiazoline)‐6‐sulphonic acid (ABTS), TPA and chlorogenic acid contents, drying caused an increase in the IN fraction of yellow figs (38, 140, 50%, respectively). The bioaccessibility of C3G and C3R were quite low for fresh figs (0–5% of the initial values), whereas for dried figs, anthocyanins were not detected at all in the IN fraction.